Perencanaan Strategis Sistem Informasi Akademik (SIAKAD) Dalam Meningkatkan Pelayanan Akademik Di Institut Agama Islam (IAI) Al-Khairat Pamekasan - Fauzan; Fajriyah; Nuris Sholeh (Proceedings of Annual Conference on Islamic Educational Management, 2021)
Academic information system (SIAKAD) is a system used to process data and conduct academic services that involve all academic civitas in higher education utilizing information systems. The use of SIAKAD in tertiary institutions is very essential especially to facilitate services both for operators and for students and lecturers. The aim of this study is to determine (1) the application of SIAKAD at IAI Al-Khairat Pamekasan; (2) the effectiveness of the use of SIAKAD at IAI Al-Khairat; and (3) the obstacles in IAI Al-Khairat Pamekasan in implementing SIAKAD.